ADAPTATION TO THE GROUND OF BLUEBERRY PLANTS (VACCINIUM MYRTILLUS L.) PRODUCED IN VITRO - Utkirova Vazira Sattarovna; Yakubov Mirakbar Daniyarovich (International Engineering Journal For Research & Development, 2022)
The cultivation of blueberries requires some technological features. When the explants were introduced in vitro, the tops of the blueberries shoots were sterilized with sodium hypochlorite. The results showed that the optimal nutrient medium for obtaining micro plants is WPM. Shoot formation was carried out on media supplemented with 1 mg/l 2iP, and for rooting 2 mg/l IBA. Our results showed that in vitro survival of plants in the soil substrate is influenced by biometric indicators of micro plants: plant height, number and length of roots. Plants with a well-developed root system take root well. The bases of ex vitro blueberry technology have been developed.